2008
DOI: 10.1111/j.1398-9995.2008.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe asthma in childhood: assessed in 10 year olds in a birth cohort study*

Abstract: The prevalence of severe asthma was 0.5% in all 10-year olds, and 4.5% among current asthmatics. The severe asthma definition applied in this study is supported by results of clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
1
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 31 publications
5
106
1
18
Order By: Relevance
“…Around 5% of children with asthma suffer from chronic symptoms and/or severe exacerbations despite treatment with a variety of drugs, including high doses of inhaled corticosteroids [1]. The term ''problematic severe asthma'' has been proposed to classify these children, of whom a subgroup suffers from severe, therapy-resistant asthma that probably requires novel therapeutic approaches [2].…”
Section: Introductionmentioning
confidence: 99%
“…Around 5% of children with asthma suffer from chronic symptoms and/or severe exacerbations despite treatment with a variety of drugs, including high doses of inhaled corticosteroids [1]. The term ''problematic severe asthma'' has been proposed to classify these children, of whom a subgroup suffers from severe, therapy-resistant asthma that probably requires novel therapeutic approaches [2].…”
Section: Introductionmentioning
confidence: 99%
“…Children with persistent symptoms and/or severe exacerbations despite high-dose treatment, especially inhaled corticosteroids (ICS), are diagnosed with PSA and may represent ∼5% of children with asthma and 0.5% in a general population-based cohort [22,23]. Clinically, it is essential to distinguish between children with PSA who present with truly severe therapy-resistant disease and those with difficult-to-treat asthma because of underlying modifiable factors such as ongoing allergen exposure, poor adherence to treatment, poor inhaler technique, smoking and comorbidities [22].…”
Section: Asthma Severitymentioning
confidence: 99%
“…The prevalence of severe asthma in childhood is largely unknown, since there is no general consensus regarding the definition, and severe childhood asthma has rarely been studied in a general population. One birth cohort study reported the prevalence of severe asthma in a general population of 10-yr-old children to be 0.5%, and 4.5 % among children with asthma [2], using a definition of poor asthma control despite prescription of 800 mg budesonide equivalent and at least a long-acting b-agonist and/or a leukotriene antagonist. However, there may be disparate underlying problems, including wrong diagnosis, poor adherence to therapy, adverse environmental conditions and comorbid conditions, such as gastro-oesophageal reflux and rhinosinusitis, as well as various forms of genuine therapy-resistant asthma.…”
mentioning
confidence: 99%